Developing IoT Devices to Catch Mouse - Inphai, Isarapong; Yenjai, kanlaya; Panawong, Naruepon (Journal of Applied Informatics and Technology, 2022)
Mice are mammals that always gnaw and destroy belongings and they can transmit diseases rapidly to humans and pets. This research aims to develop an IOT device to trap a mouse by using applied internet technology of things. There are two types of applied sensors in the device that are Ultrasonic Sensors and IR Sensors. If a mouse is into a mousetrap device, both sensors will send a signal to ESP32 DevKit V1 board to order the Servo Motor to close the device door. The board then sends a notification message to the user's LINE application. The user can also control an on-off module through the Blynk application. From the results of testing the accuracy of the mousetrap device’s operation, it was found that the average accuracy was 95.5%, the users’ satisfaction was 90.2%. And the results of comparison of the two devices found that devices using infrared sensors would perform better than devices with ultrasonic sensors.